Study of prevalence and prescribing trends in infectious diseases: as a teaching tool for MBBS 2nd professional students - Beg, Mirza A.; Dutta, Shakti B.; Bawa, Shalu; Kaur, Amanjot; Vishal, Subhash (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Irrational prescription of drugs is a common occurrence in clinical practice. Introduction of clinical pharmacology at the undergraduate level as an integral part of rational therapeutics is the need of hour. The present drug utilization study, prevalence and prescribing pattern in infectious diseases in a tertiary care teaching hospital was carried out to teach clinical pharmacology to 2nd professional MBBS students, to sensitize and promote rational prescribing. Methods: A total of 621 prescriptions were collected by 2nd professional MBBS students at Shri Guru Ram Rai Institute of Medical and Health Sciences, Dehradun. Prescriptions were analyzed on various parameters, using WHO drug use indicators. Results: A total of 621 prescriptions were analyzed. 477 (76.81%) were males and 144 (23.19%) were females. Majority of patients 357 (57.49%) were 16-60 years’ age group. The infectious diseases prevalence was 153 (24.63%) enteric fever, 132 (21.26%) hepatitis, 111 (17.87%) pyrexia of unknown origin, 90 (14.49%) cellulitis, 135 (21.74%) belongs to miscellaneous category respectively. A total of 4446 drugs were prescribed, which includes antibiotics 2025 (45.55%), multivitamins 969 (21.79%), antacids 699 (15.72%), analgesics 408 (9.18%), antiemetic 273 (6.14%) and antiepileptic 72 (1.62%) respectively. 3096 (69.64%) oral, 1350 (30.36%) injectable and 786 (17.68%) fixed dose combinations (FDCs) were prescribed. 3.26 antibiotics and 7.15 drugs per prescription were prescribed. 2622 (58.97%) drugs were prescribed from national essential medicine list 2015. 100% drugs were prescribed by brand names. Conclusions: The prescriptions revealed polypharmacy. This study can help to provide feedback to the prescribers, thereby increase in awareness and improve patient care by rational utilization of drugs.